Plan de negocios para la implantación de un servicio de parqueaderos en la ciudad de Quito, ubicado entre las avenidas República de el Salvador y Shyris - Velasteguí Utreras, Francisco Javier (2011)
The business idea is to implement a parking service at Av Republic of El Salvador and Shyris. Chapter one investigates and analyzes the environment where the industryshows stable growth levels. We also studied the same variables, such as the regulation of the peak and plate number of vehicles registered, among others. In this chapter, discussed the business with respect to Porter's five competitive forces, which allowed the respective SWOT develop. It describes the business idea, where your main objective is to provide the public a parking service that meets their needs over time. After the environment was conducted market research, where the results were positive, generating business opportunity. Respective segmentation was performed. The chapter excels marketing plan to sell the business flow, which enables to optimize the relationship with the client. We defined the brand, which has colors intended to attract the customer and defined the slogan, which is directly linked with the main objective of the business. A plan of operations, where strategic planning was conducted for each functional area of business, a flowchart of internal procedures and the value chain. We analyzed the relevant legal and regulatory issues, concluding that the business is feasible in terms of regulatory and legal terms. Contingency actions were proposed to counteract effects a change in preferences of consumers in less use of the parking lot to the program, funding problems, in some cases of theft, fire, flood, among others. Finally, the financial analysis gave positive results, giving an internal rate of return unfunded plan of 20.1%, 23.6% and 26.4%, while finance it gives an internal rate of return of 26.1% 27.6% and 31.3% in the pessimistic scenario, normal, optimistic, respectively. The business is viable and should be carried out.